Similar sensitivity of time to exhaustion and time-trial time to changes in endurance - Amann, M.; Hopkins, W. G.; Marcora, S. M. (Medicine & Science in Sports & Exercise, 2008)
Purpose: There is widespread misunderstanding about the ability of constant-power tests to quantify changes in endurance performance. We have therefore compared the sensitivity of a constant-power test with that of a time trial for the effects of arterial oxygenation on endurance performance.